How are the interoperability requirements addressed in the Systems-of-Systems context? - Costa, Murilo Gustavo Nabarrete; Paiva, Débora Maria Barroso; Cagnin, Maria Istela (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context:To achieve economic advantages and broader business goals, organizations participate in mergers, acquisitions or joint ventures processes, aiming to form alliances of organizations. In this context, when integrating the information systems of these organizations, Systems-of-Systems (SoS) arise. Each constituent system of SoS has its own business goals. When these systems interoperate among them, they contribute to achieving the SoS missions and the strategic business goals of alliances. Problem:However, the interoperability among the constituents is a challenge as the discovery of interoperability requirements is an open question, because of the complexity of SoS Requirements Engineering, mainly due to SoS heterogeneity and dynamism. Solution:The main contribution of this paper is to investigate how SoS interoperability requirements are being extracted, specified, and validated in the literature. Method:A systematic literature review has been conducted based on the process proposed by Kitchenham. Summary of Results:Most of the found solutions extract SoS interoperability requirements at the architectural level and adopt particular techniques for specification mainly based on matrices. Besides that, we did not find any evidence about the requirements validation. Contributions and Impact in the IS area:The main contribution of this work is to shed light on the main techniques used to handle the SoS interoperability requirements and evidence the urgency of the establishment of proper methods and techniques for SoS Interoperability Requirements Engineering, considering the alignment between the business and technical levels.